Balanceamento da carga de um fluxo em múltiplos caminhos usando conceito de redes par-a-par - Assumpção, Jorge Henrique de Barros (2012)
The Internet suffer an increased amount of traffic. This increase could affect the structure of computer networks generating packet losses and delays. This loss and delay stems from the packet flows that generate more traffic that particular path or subpath, can support. Given this situation we show in this paper a mechanism based on P2P that balances the load by using multiple paths along with the breaking of the flow in smaller streams. For this mechanism called P2P-Flow that can be implemented in OpenFlow. In our simulation we compare this mechanism with multicast and unicast in multiple scenarios. The contributions of this work are detailed in the idea P2PFlow and compared with the multicast and unicast topology in various scenarios.